Corrective Feedback and Students Uptake In Writing Recount Text at SMPN 1 Kampar - Widia Rahma Yuni; Masrul (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to determine students' writing skills where the results were obtained through interviews with English subject teachers. The writing skills of students identified, especially errors in using grammar in writing recount text, were obtained from the results of interviews with subject teachers who had corrected the results of students' recount text writing. The method used in this research is a qualitative method by conducting interviews with English subject teachers. One English subject teacher was chosen as a participant. Data were collected through semistructure interviews with subject teachers. The results showed that from the analysis of the students' writing by the teacher, the results were not good. Students make mistakes in using grammar, such as using tobe, verbs, conjunctions and writing simple past tense sentences.